Manipulation of interlayer spacing and surface charge of carbon nanosheets for robust lithium/sodium storage. (November 2019) - Gao, Cai; Feng, Jianze; Dai, Jingrou; Pan, Yuanyuan; Zhu, Yulong; Wang, Wenhang; Dong, Yunfa; Cao, Linfang; Guan, Lu; Pan, Lei; Hu, Han; Wu, Mingbo
Abstract: The sluggish kinetics in anode materials severely prevents the practical use of lithium/sodium-ion batteries in many current and emerging applications. To overcome this bottleneck, we report a facile and scalable strategy to construct nitrogen and phosphorus co-doped carbon nanosheets with abundant electron-rich regions rendering a strong cation attraction and expanded interlayer spacing for fast lithium/sodium diffusion, which allows excellent rate capable anodes for lithium/sodium-ion batteries. Specifically, the as-prepared nanosheets afford outstanding pseudocapacitive behavior with superior rate capacities of 379 and 140 mA h g −1 at a high current density of 5.0 A g −1 for lithium and sodium storage, respectively, while the calendar life can be as long as thousands of cycles. The extraordinary rate capability is further demonstrated through combined use of quantitative kinetics analysis, galvanostatic intermittent titration technique measurements and theoretical simulation. Considering the extraordinary electrochemical performance and comprehensive analysis of pseudocapacitive lithium/sodium storage mechanism, this work holds great potential to serve as a fundamental reference for exploring robust pseudocapacitive electrode materials. Graphical abstract: Image 1